Citizen Participation, Perceived Public Service Performance, and Trust in Government: Evidence from Health Policy Reforms in Hong Kong. Issue 3 (4th May 2021) - He, Alex Jingwei; Ma, Liang
Abstract: Citizen participation is advocated as an effective instrument to retain and promote government legitimacy, but to what extent and through what mechanisms participation affects government trust have not been fully elaborated. In this study, we examine the mediating role played by perceived government performance in the link between citizen participation and government trust, by analyzing data from Hong Kong. We seized the opportunity when the Hong Kong SAR Government was undertaking public consultation on a health financing reform proposal and collected data from a telephone survey of adult citizens. Empirical evidence reveals that citizens who believe that their opinions about health care reform are considered by the government are more satisfied with health system performance, which, in turn, leads to stronger trust in government. If designed and executed properly, citizen participation in health policy generates positive outcomes, enhancing the legitimacy of health policy and that of government as a whole. The theoretical and policy implications of the empirical results are discussed with reference to the value of citizen participation and the political ramifications of social policies.